PENGARUH REGULASI EMOSI TERHADAP PERILAKU HOMESICKNESS PADA MAHASISWA RANTAU FIPP UNIMA ANGKATAN 2023 DAN 2024 - Birgita Massang, Meylinda; M. Tiwa, Tellma; B. Sengkey, Stevi (Penerbit Lafadz Jaya, 2026)
Migrant students often experience homesickness during initial adaptation to university life away from family, manifesting as emotional distress including sadness, anxiety, and reduced motivation. This study aimed to examine the effect of emotion regulation on homesickness behavior among Faculty of Education and Psychology migrant students at Universitas Negeri Manado cohorts 2023-2024. Quantitative research with associative design was employed, targeting a population of all migrant students from these cohorts and purposive sampling of 75 respondents. Data collected via 63-item Likert scale questionnaire on emotion regulation and homesickness were analyzed using simple linear regression, normality, linearity tests via SPSS 24. Results revealed a significant negative effect (β = -0.648, t = 12.007, p < 0.05) with emotion regulation contributing 64.7% to homesickness variance. In conclusion, stronger emotion regulation skills substantially reduce homesickness intensity, suggesting emotion regulation training as essential for migrant student adaptation.